SIMULATION-BASED RAM DESIGN OF A MULTI-UNIT SYSTEM WITH HYBRID GENETIC ALGORITHM - Han, Young Jin; Yun, Won Young (International Journal of Industrial Engineering: Theory, Applications and Practice, 2017)
In this paper, we deal with a RAM design problem for a multi-unit system, and consider system availability and life cycle cost as optimization criteria, which are estimated by simulation. The objective of this study is to determine the values of MTBF of all the components, ALDT of the system, as well as the maintenance units and times that minimize life cycle cost and satisfy target system availability. A hybrid genetic algorithm with a heuristic method is proposed to find alternative design parameters. Numerical examples are studied to investigate the effect of variations in model parameters on optimal solutions.